2018
DOI: 10.1136/bjophthalmol-2018-312018
|View full text |Cite
|
Sign up to set email alerts
|

Lack of tumour pigmentation in conjunctival melanoma is associated with light iris colour and worse prognosis

Abstract: Lightly pigmented tumours occurred especially in individuals with lightly coloured irises. While iris colour or skin colour was not significantly related to clinical outcome, a low tumour pigmentation was related to a worse outcome in patients with conjunctival melanoma. The amount and type of melanin in conjunctival melanocytes may be involved in the pathogenesis and behaviour of selected conjunctival melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 27 publications
0
10
1
Order By: Relevance
“…As reported in our earlier study of a predominantly Caucasian population with CoM, 60% of all primary lesions were of high pigmentation and 40% were of low pigmentation [10]. This is significantly different from the percentages found in recurrent lesions of the same study population: 46 patients (39%) had exclusively pigmented lesions during follow-up, and 71 patients (61%) had non-pigmented or mixed lesions at some moment during follow-up.…”
Section: Discussioncontrasting
confidence: 69%
See 3 more Smart Citations
“…As reported in our earlier study of a predominantly Caucasian population with CoM, 60% of all primary lesions were of high pigmentation and 40% were of low pigmentation [10]. This is significantly different from the percentages found in recurrent lesions of the same study population: 46 patients (39%) had exclusively pigmented lesions during follow-up, and 71 patients (61%) had non-pigmented or mixed lesions at some moment during follow-up.…”
Section: Discussioncontrasting
confidence: 69%
“…A data set of 444 patients diagnosed with primary CoM from the Wills Eye Hospital (Philadelphia, USA) and the Leiden University Medical Center (Leiden, The Netherlands) was analysed. Patient and tumour characteristics of this combined set have been previously published [10]. In short, all patients had histopathologically confirmed CoM, the mean age of these patients was 59.5 years (SD 17.5), 51% was female, the mean tumour thickness was 1.77 mm (SD 2.1) and 63% of lesions were epibulbar.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies showed that low-pigmented CM is seen more frequently in eyes with light iris color and is associated with a higher rate of recurrences, distant metastases and death. Thus, it has been hypothesized that a low tumor pigmentation is associated with worse outcomes (17), with a possible link between eumelanin/pheomelanin ratio and the grade of severity of CM. It is possible, however, that worse outcomes occur in pale tumours because they mimic other entities such as OSSN and definitive management is delayed.…”
Section: Discussionmentioning
confidence: 99%